2016
DOI: 10.1016/j.eurpsy.2016.01.709
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dialectical behavior therapy on incidence of suicidal attempts and non-suicidal self injury among a sample of Egyptian borderline personality disorder patients

Abstract: IntroductionDialectical behavior therapy (DBT) is a comprehensive psycho-social treatment developed by Marsha Linehan and originally designed for persons meeting criteria for borderline personality disorder (BPD). DBT is considered as a standard evidence based treatment for suicidal BPD patients in most international guidelines. Although its effectiveness has been proved in multiple studies across different patient populations but almost all the research was conducted in North American or European countries. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Currently, there are several studies on the efficacy of DBT in Egypt where 90% of the population is Muslim (Office of International Religious Freedom, 2019). The studies (Abdelkarim et al, 2016(Abdelkarim et al, , 2017Fnoon et al, 2021) indicate that DBT is effective for borderline personality disorder, substance use, suicidal attempts, nonsuicidal self-injury, and emotion regulation. However, none of the studies reported their participants' religion.…”
Section: Mindfulness-based Interventionsmentioning
confidence: 99%
“…Currently, there are several studies on the efficacy of DBT in Egypt where 90% of the population is Muslim (Office of International Religious Freedom, 2019). The studies (Abdelkarim et al, 2016(Abdelkarim et al, , 2017Fnoon et al, 2021) indicate that DBT is effective for borderline personality disorder, substance use, suicidal attempts, nonsuicidal self-injury, and emotion regulation. However, none of the studies reported their participants' religion.…”
Section: Mindfulness-based Interventionsmentioning
confidence: 99%